Spanish in contact with Korean: New insights into language switching - Kim, Silvia (Universidad Pedagógica y Tecnológica de Colombia, 2020)
‘Code-switching’ (CS) refers to language-mixing where individuals who speak two or more languages switch from one to another, often mid-sentence. Several morpho-syntactic constraints governing when switches happen have been proposed in prior work, mostly on Spanish-English CS (e.g. Timm, 1975; Pfaff, 1979; Poplack, 1980). However, what happens when the languages are typologically different? This is the case with Spanish-Korean CS, which has not been systematically investigated. Korean and Spanish differ in many respects, including clause structure/word order, absence/presence of articles, and morphology (Korean: agglutinative, Spanish: fusional) (Kwon, 2012; Bosque, Demonte, Lázaro, Pavón & Española, 1999). For the present study, balanced Spanish-Korean bilinguals were interviewed to obtain a naturalistic corpus of CS. Strikingly, we find that many constraints proposed for Spanish-English CS do not hold for Spanish-Korean. Specifically, there are three main ways that Spanish-Korean CS violates the constraints proposed for Spanish-English: (i) in contexts involving word order/clause structure, (ii) on the level of nouns and (iii) on the level of morphemes. Crucially, the violations are not random: We suggest that they stem from the typological differences between Korean and Spanish. This work highlights the empirical and theoretical benefits of including typologically diverse language pairs when investigating CS.